2014
DOI: 10.1016/j.esd.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Field trial testing of an electricity-producing portable biomass cooking stove in rural Malawi

Abstract: A novel off-grid electricity-producing device has been designed for integration with biomass-fuelled improved cooking stoves commonly in use in the developing world. The device operates on the thermoelectric principle whereby small amounts of electricity can be produced in response to a temperature difference across a thermoelectric generator, or TEG. The energy produced by the integrated generator can be used for direct charging or stored in a rechargeable lithium-ironphosphate (LiFePo4) battery. The generato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…The circuitry used to charge the lithium-iron-phosphate battery is designed to be as simple as possible. Previous studies using this basic circuit have shown that the system approaches the maximum power point when the temperature difference across the TEG is close to or above 150°C (Kinsella et al, 2014;O'Shaughnessy et al, 2014). Sophisticated maximum-power-point-tracking (MPPT) techniques such as those investigated in Ko Ko et al (2011), Montecucco and Knox (2015), Sungkyu et al (2010), and Xiaodong et al (2010) were not employed.…”
Section: Battery Charging Circuitrymentioning
confidence: 98%
See 1 more Smart Citation
“…The circuitry used to charge the lithium-iron-phosphate battery is designed to be as simple as possible. Previous studies using this basic circuit have shown that the system approaches the maximum power point when the temperature difference across the TEG is close to or above 150°C (Kinsella et al, 2014;O'Shaughnessy et al, 2014). Sophisticated maximum-power-point-tracking (MPPT) techniques such as those investigated in Ko Ko et al (2011), Montecucco and Knox (2015), Sungkyu et al (2010), and Xiaodong et al (2010) were not employed.…”
Section: Battery Charging Circuitrymentioning
confidence: 98%
“…Power to the 12 V fan/motor assemblies was supplied with an Aim-TTi EX2020R desktop power supply. For all modified fan tests, power was supplied by the TEG and accompanying circuit almost identical to that described in O'Shaughnessy et al (2014).…”
Section: Heat Sink Selectionmentioning
confidence: 99%
“…In terms of risks associated with developing such a water services strategy, those related to evidence of the community's 'willingness to pay' are significant. For example, a wide range of variables can influence empirical evidence of willingness to pay [73], which need to be explored in further work around suitable business models. Such variables as respondents' age, household size and occupation of the household head have been shown to be significant factors in determining willingness to pay for water services.…”
Section: Knowledge On Renewable Energy Sourcesmentioning
confidence: 99%
“…This can be accomplished by collecting the energy of solar radiation to heat on hot side of TEC and cool it by heat sink on the other side, then the electricity is generated [3]. Several TEC-based heat-to-electricity converters have been proposed and demonstrated for battery charging and lighting purposes under different infrared sources such as heat generators [4], automotive [5], candles [6], wood burning stoves [7-8], camp fire [9], and cooking stoves [10][11][12][13]. Particularly, there are new designed cooking stoves which can directly receive heat and convert it to electricity by itself [10] and can directly collect heat from biomass [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several TEC-based heat-to-electricity converters have been proposed and demonstrated for battery charging and lighting purposes under different infrared sources such as heat generators [4], automotive [5], candles [6], wood burning stoves [7-8], camp fire [9], and cooking stoves [10][11][12][13]. Particularly, there are new designed cooking stoves which can directly receive heat and convert it to electricity by itself [10] and can directly collect heat from biomass [11][12][13]. Because the use of a heat sink and a cooling fan for heat dissipation at the cold side of the TEC is not enough to cool it downs, these modules cannot be operated for a long time as an electronic power supply.…”
Section: Introductionmentioning
confidence: 99%